Planning for teaching and learning. Understanding and working with syllabi used in schools, lyceums and colleges - Egamberdiyeva Marxabo (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This paper discusses the importance of effective planning in the teaching and learning process, with a focus on understanding and working with syllabi used in schools, lyceums, and colleges. It explores how a well-structured syllabus serves as a roadmap for educators, helping them organize content, set learning outcomes, and manage time efficiently. The abstract highlights the key components of syllabi and emphasizes the need for teachers to adapt them to meet students’ needs while aligning with educational standards. By developing skills in syllabus analysis and lesson planning, future educators can create engaging and goal-oriented learning experiences.